Productive pedagogies for reforming secondary school mathematics classroom practice in Nigeria - Bature, Iliya Joseph (Curtin University, 2014)
This study adopted qualitative case study to investigate the effectiveness of introducing Productive Pedagogies into Nigerian mathematics classroom. It involved providing scaffolding, implementations, reflections, perceptions and challenges encountered while introducing the framework. Efforts were made to demonstrate Productive Pedagogies during classroom instruction which was evident in the activities created to increase student-centred learning. This suggests that Productive Pedagogies is a useful tool for improving teachers’ teaching skills, students’ engagement and collaboration.